The Influence of E-Learning as a Complement on Student Learning Satisfaction in Batam - Prasetyo, Stefanus Eko (Universitas Medan Area, 2019)
The utilization of e-learning as a complementary learning requires careful consideration by the Higher Education, so that e-learning can provide benefits and improve student satisfaction, especially employee class students in Batam City. The aim of the study was to find out whether there was an effect of expediency, ease of use, social influence, and conditions of supporting facilities on student learning satisfaction in using e-learning as a complementary learning tool in Batam City. Data was taken from random distribution of questionnaires to 207 respondents of students of Information Systems Study Program Batam International University and Putera Batam University who used e-learning as a complement to learning. Research uses a quantitative approach. Data were analyzed by multivariate multiple regression analysis. The results of the analysis show the significance of Benefit 0,000 with a coefficient of 0.322, significance of Ease of Use 0,000 with coefficient of 0.286, significance of Social Influence 0.002 with coefficient of 0.187 and significance of Conditions of Supporting Facilities 0.001 with coefficient of 0.197. It can be concluded that usefulness, ease of use, social influence and conditions of supporting facilities have a significant positive influence on learning satisfaction.